Hypoxia-Inducible Non-coding RNAs in Mesenchymal Stem Cell Fate and Regeneration - Ye, Yu; Zhao, Xinyuan; Xu, Yan; Yu, Jinhua (Frontiers in Dental Medicine, 2021)
MSCs can differentiate into multiple cell lines, which makes them an important source of cells for tissue engineering applications. They are defined by the capability to renew themselves and maintain pluripotency. This ability is modulated by the balance between complex cues from cellular microenvironment. Self-renewal and differentiation abilities are regulated by particular microenvironmental signals. Oxygen is considered to be an important part of cell microenvironment, which not only acts as a metabolic substrate but also a signal molecule. It has been proved that MSCs are hypoxic in the physiological environment. Signals from mesenchymal stem cell microenvironment or niche which means the anatomical location of the MSCs, maintain the final properties of MSCs. Physiological conditions like oxygen tension are deemed to be a significant part of the mesenchymal stem cell niche, and have been proved to be involved in modulating embryonic and adult MSCs. Non-coding RNAs (ncRNAs), which play a key role in cell signal transduction, transcription and translation of genes, have been widely concerned as epigenetic regulators in a great deal of tissues. With the rapid development of bioinformatics analysis tools and high-throughput RNA sequencing technology, more and more evidences show that ncRNAs play a key role in tissue regeneration. It shows potential as a biomarker of mesenchymal stem cell differentiation. In this paper, we reviewed the physiological correlation of hypoxia as a unique environmental parameter which is conducive to mesenchymal stem cell expansion and maintenance, discussed the correlation of tissue engineering, and summarized the influence of hypoxia related ncRNAs on MSCs' fate and regeneration. This review will provide reference for future research of mesenchymal stem cell regeneration.